Developing a Curiosity-Centered Pedagogy for Music Technology - Jeff Kaiser (Journal of the Association for Technology in Music Instruction, 2025)
Two of the foundations of learning are attention and active engagement, the latter being “an algorithm also called curiosity” (Dehaene 2021, p. 145). Curiosity is fundamental to being human, encourages exploration, and when curiosity is engaged, optimizes learning. We know that a person who is not engaged does not learn as much “because learning requires an active generation of hypotheses…” (Dehaene 2021, p. xxvii) as well as testing and refining these hypotheses through exploration. Curiosity motivates and deepens this process. In music technology, we have the attention of our students, as the relevance and meaningfulness of our area of study are readily apparent in popular culture and are hopefully made even more clear in the classroom. Knowing this attention is present, I will explore how we can use music technology to best engage the algorithm called curiosity and increase the level of active engagement. Contrarily, I will interrogate and give examples of how we—as professors in programs focusing on music technology—can crush curiosity in students and how to avoid this.
Keywords: pedagogy; technology; curiosity